REPRESENTATION OF POVERTY AND SOCIAL DISCRIMINATION IN THE NOVEL ‘THE GRAPES OF WRATH’ BY JOHN STEINBECK (1939) - Muhammad Taufik; Helmi Syukur; Nasrum; Syakirah Rahmah (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This research explores the themes of poverty and social discrimination in John Steinbeck's work entitled 'The Grapes of Wrath' through the perspective of Marxist theory. By using qualitative methods, including and in-depth understanding, this research investigates the content of the extent to which the characters' analytical experiences are in line with Karl Marx's views on class struggle. Findings show emotional representations of poverty, depicted through the return of a person recently released from prison to meet basic needs, and social discrimination, such as the rejection of homeless groups as local residents. This research deepens the understanding of economic structures and dominance interactions, providing insight into the complex relationship between societal forces and individual experiences in this novel. The aim of this research is to understand the various forms of poverty and social discrimination by utilizing the Marxist theory proposed by Karl Marx.